A peptide switch regulates DNA polymerase processivity - López de Saro, Francisco J. (National Academy of Sciences, 2003)
Chromosomal DNA polymerases are tethered to DNA by a circular sliding clamp for high processivity. However, lagging strand synthesis requires the polymerase to rapidly dissociate on finishing each Okazaki fragment. The Escherichia coli replicase contains a subunit (τ) that promotes separation of polymerase from its clamp on finishing DNA segments. This report reveals the mechanism of this process. We find that τ binds the C-terminal residues of the DNA polymerase. Surprisingly, this same C-terminal “tail” of the polymerase interacts with the β clamp, and τ competes with β for this sequence. Moreover, τ acts as a DNA sensor. On binding primed DNA, τ releases the polymerase tail, allowing polymerase to bind β for processive synthesis. But on sensing the DNA is complete (duplex), τ sequesters the polymerase tail from β, disengaging polymerase from DNA. Therefore, DNA sensing by τ switches the polymerase peptide tail on and off the clamp and coordinates the dynamic turnover of polymerase during lagging strand synthesis.